PARASITOID AGRIBUSINESS COOPERATION (PAC); OPTIMIZING PARASITOIDS THROUGH MASS PRODUCTION AND INSTITUTIONAL MANAGEMENT AGAINST RICE STEM BORER ATTACK AS A HOLISTIC EFFORTIMPROVING FARMERS' WELFARE - Fariz Kustiawan Alfarisy; Hari Purnomo; Suharto Suharto (Indonesian Journal of Fundamental Sciences, 2018)
The purpose of this study is to determine the potential of parasitoids through mass production and management of farm institutions to improve the welfare of farmers. The results showed the total number of parasitoids found 385 of the four locations. The found parasitoids consist of Trichogramma spp and Telenomus spp. Parasitoid populations were found to potentially parasitize stemborer eggs as a control effort. The highest level of parasitation lies in Mumbulsari sub-district at 65%. The highest abundance lies in Mumbulsari sub-district with 10.7 heads. This indicates the abundance of parasitoids at these locations is abundant. The success of mass production techniques also requires the management of peasant institutions.